Makna Denotasi dan Konotasi Dalam Puisi ‘Iqbal wa Al-lail’ Karya Badr Shaker Sayyab: Kajian Semantik - Pratama, M. Maulana Kurnia (Universitas Lampung, 2024)
This study aims to describe the connotative and denotative meanings in the poetry of Badr Shaker Sayyab. This type of research is qualitative research. The object of this research is the poem 'Iqbal wa Al-Lail' by Badr Shaker Sayyab. The data collection technique in this research employed the observation method. The data analysis used in this study is content analysis. This technique involves reading, recording (words, phrases, and symbols), and closely examining each stanza of the poem repeatedly to identify denotative and connotative meanings. The findings of this research reveal denotative and connotative meanings in the early stanzas that depict the author's state during the night. In the 4th verse and onwards, Badr Shaker Sayyab feels a lot of sadness with affirming sentences directed towards his beloved and the desire to feel the happiness previously felt. That's why this poem contains many connotative meanings.Keywords: Semantic Analysis, Denotative, Konotative, Poetry